Assessment of Adiantum incisum, Alternanthera pungens and Trichodesma indicum as Bio-insecticides against Stored Grain Pests: Plants as Bio-insecticides - Kazmi, Zehra; Safdar, Naila; Yasmin, Azra (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
This study investigated the insecticidal potential of Adiantum incisum Forssk (Pteridaceae), Alternanthera pungens Kunth (Amaranthaceae) and Trichodesma indicum L. (Boraginaceae). Aqueous, methanolic and n-hexane extracts of whole plants (roots, stem and leaves) were prepared using maceration technique. Insecticidal activities of aqueous, methanolic and n-hexane extracts of three plants (10, 20 and 30 mg/mL) were evaluated by impregnated filter paper insecticidal assay. Methanol and hexane extracts of Adiantum incisum gave effective LD50 (15.3 mg/mL) against Callosobruchus chinensis and Sitophilus oryzae (LD5022 mg/mL) after 24 hours respectively. Present research elucidates the important phytochemicals (alkaloids, saponins and tannins) in three plants by FTIR and good insecticidal activity (LD50 < 25 mg/mL in 24 hours) against Callosobruchus chinensis and Sitophilus oryzae. Current study promotes further investigations for using these plant extracts as anti-feedants, repellents, fumigants and formulation of nontoxic bio-insecticides.